Pengaruh Penyuluhan Kesehatan terhadap Perilaku Pencegahan Kekambuhan Gastritis pada Santriwati PMDG Putri 2 - Muliska Jumiatun Nikmah; Nadia Iha Fatihah; Amal Fadholah (University Of Darussalam Gontor, 2022)
Gastritis is one of the biggest problems that most often occurs in everyday life. According to WHO, the incidence of gastritis in Indonesia reached 40.8%. The purpose of this study is to find out the effect of health counseling on the behavior of preventing gastritis recurrence. The method used is non probability sampling with purposive sampling techniques experimenting with control group pretest and posttest designs. The researchers divided the two groups: the experimental group and the control group. The sample in this study was 40 Students Gontor For Girl Second Campus who had experienced gastritis disease, in the experimental group there were 20 samples and the control group there were 20 samples. The data analysis in this study used the Wilcoxon test with SPSS 16.0 with a significance level of 95%. Based on the results of Wilcoxon's statistical test on behavioral variables obtained a significance value of p = 0.000 (p<0.05) while in the knowledge variable obtained a significant value of p = 0.001 (p<0.05) that there is an influence of health counseling with audio visual methods and leaflets. The conclusion of this study is that there is an effect of health counseling on knowledge about the prevention of gastritis recurrence in Gontor Putri 2 santriwati with a signification value of p = 0.001 (p<0.05) and there is an effect of health counseling on the behavior of preventing gastritis recurrence in Students Gontor For Girl Second Campus with a significance value of p = 0,000 (p<0.05).